STUDI LITERATUR: METODE PEMBELAJARAN BAGI SISWA SEKOLAH DASAR DENGAN GANGGUAN SENSORIK - Ayu Wida Aulia Sari; Ghari Sulistiani; Linna Afara; Siti Naurah Laila Rasyidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to use appropriate learning methods for teachers for elementary school students with eye sensory disorders. The method used is qualitative research, literature review/literature study method. By examining 7 data with similar categories. The results of the discussion from this research are that several choices of appropriate and varied learning methods can have a significant impact on understanding and cultivating successful learning for students with visual impairment or visual impairment. Apart from that, it also creates a better teaching and learning process with the final results as expected.